PERSEPSI DAN MOTIVASI PENGUNJUNG TERHADAP PEMANFAATAN HUTAN KOTA SRENGSENG SEBAGAI OBJEK WISATA (Visitor’s Perception and Motivation Towards the Use of Srengseng Urban Forest as A Tourist Attraction) - Angreyani, Fenny; Hasibuan, Ratna Sari; Sasongko, Dwi Agus (Jurnal Nusa Sylva, 2023)
Srengseng Urban Forest is one of the types of Green Open Space (RTH) with tourism potential that is worthy of being developed. This can be seen from the adequate views of the forest and lake, easy access to the location, and can be a means of recreation for the surrounding community. Srengseng Urban Forest is one of the important areas that should be considered in order to create a comfortable city layout. In order to achieve a comfortable city forest for visitors, data is needed regarding visitor perceptions and motivations. The purpose of this study was to determine the perceptions and motivations of visitors to Srengseng Urban Forest. The study used a qualitative method through interviews using a closed questionnaire. The research respondents numbered 90 people, who were determined using the Slovin Technique. The assessment of the results was analyzed using the Likert Scale. Data collection used was to search for, record, and collect all information objectively and as it is according to the results of observations and interviews in the field, namely data recording and various forms of data in the field. Visitor perceptions of Srengseng Urban Forest in the categories of knowledge, comfort and security, security and safety, cleanliness, and facilities are in the good and very good categories. Visitor motivation in Srengseng Urban Forest on the driving factors is dominated by recreational and sports activities. Meanwhile, the pull factors are dominated by proximity to the visitor's residence as well as the coolness and comfort of the place.